Protótipo de sistema audível para deficientes visuais na identificação de recipientes de coleta seletiva - Silva Filho, Walkernandes Ferreira da (Universidade Federal Rural do Semi-Árido, 2018)
In order to reduce the existing barriers that the visually impaired face day by day, a prototype was developed with the purpose of facilitating the identification of selective collection containers by the visually impaired, through the reproduction of sound effects that can facilitate and make practical their understanding. We used an ultrasound sensor, a microcontroller board called Arduino Mega2560, a micro SD card reader and other electronic devices. The reason for choosing the Arduino Mega was because of its easy workability, it has a great cost benefit and several libraries ready in which they have greatly facilitated the construction of this prototype. The programming language used was C, which is used by Arduino software. The ultrasonic sensor was chosen for its high economic viability and functionality. The programmed condition for the prototype to work was that: As an individual enters the radius of the ultrasound sensor and the preset distance of 200cm or less from the sensor, a sound would be reproduced indicating which type of collection vessel selective visual impairment would be. In the initial idea, it would be used of a load sensor and an amplifier module HX711, however its initial construction was not completed and some substitutions were made. All the tests done for the prototype were attended to, the ultrasonic sensor easily captured the distance and the audio reproduction got a sharp quality for your understanding.
Monografia
Keywords: Deficiente visual; Protótipo; Coleta seletiva; Sensor ultrassom; Arduino; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA